2013
DOI: 10.1016/j.postharvbio.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the improvement in rachis quality by high CO2 levels in table grapes stored at low temperature

Abstract: Rachis browning is one of the main factors reducing the quality of table grapes during storage at low temperature. To better understand the effect of a 3-day CO 2 pretreatment (20% CO 2 plus 20% O 2 ) on maintaining the rachis quality of table grapes (Vitis vinifera cv. Cardinal) 5 at 0 ºC, we analyzed the expression of genes codifying enzymes related to the synthesis and oxidation of phenolic compounds (phenylalanine ammonia-lyase, VcPAL; and polyphenol oxidase, GPO) and the detoxification of reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 49 publications
7
46
0
Order By: Relevance
“…However, this decrease was noticed in CO 2 ‐treated SS samples, whereas the gene expression did not change in fruit stored in air. A previous study indicated that the beneficial effect of the pretreatment with high CO 2 levels to control oxidative stress by the induction of the enzymatic antioxidant system depends on the type of tissue . Although we had previously suggested that APX participates in removing the putative high levels of H 2 O 2 in the skin of non‐treated Cardinal grapes, in the case of AR and SS this fact seems to be due to CAT .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…However, this decrease was noticed in CO 2 ‐treated SS samples, whereas the gene expression did not change in fruit stored in air. A previous study indicated that the beneficial effect of the pretreatment with high CO 2 levels to control oxidative stress by the induction of the enzymatic antioxidant system depends on the type of tissue . Although we had previously suggested that APX participates in removing the putative high levels of H 2 O 2 in the skin of non‐treated Cardinal grapes, in the case of AR and SS this fact seems to be due to CAT .…”
Section: Resultssupporting
confidence: 80%
“…Similarly, chitosan coating positively influenced the physical–chemical and nutraceutical traits of three strawberry cultivars, reducing postharvest oxidative stress through the increase of APX activity but not CAT . However, we have observed that the beneficial effect of the CO 2 treatment in controlling oxidative stress by modulating genes implicated in the enzymatic antioxidant system was closely related with the reduction of rachis browning rather than with a general response in table grapes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work, we observed that the development of rachis browning in non-treated table grapes was linked to an induction of ACS1 and ACO1 gene expression. By contrast, ACO1 and ACS1 transcript levels were markedly induced in grape skin treated with high CO 2 levels, while in non-treated skin the induction was lower or appeared later during storage (Rosales et al, 2013). We analyzed the correlations between the expression of ACO1, ACS1 and the five VviERFs-c in fruit and non-fruit tissues of treated and non-treated table grapes stored at 0°C and did not find any significant result (data not shown), not being able to establish a relationship between the expression of ethylene biosynthetic genes and VviERFs-c .…”
Section: Discussionmentioning
confidence: 98%
“…DQ267094) were assayed using quantitative real-time RT-PCR (RT-qPCR) with samples of skin, pulp, seed, and rachis from CO 2 -treated and non-treated bunches stored for 0, 3, and 15 days at 0°C. RT-qPCR was performed as described by Rosales et al (2013) using Actin1 from V. vinifera (ACT1: XM 002282480) as the internal control. Gene-specific primers pairs for RT-qPCR (Supplementary Table S1) were designed with Primer 3 software (Koressaar and Remm, 2007).…”
Section: Methodsmentioning
confidence: 99%